An approach to multi-attribute negotiation between semantic web services. (22nd September 2009) - Kumar, Sandeep; Mishra, R.B.
In a semantic web-based system, before taking the services of a Service Provider (SP), the requester may need to negotiate with it on various issues. This paper presents a Multi-Attribute Negotiation (MAN) approach for negotiation between Semantic Web Services (SWSs). The communication model along with the algorithms for various actions involved in the negotiation process is described. A novel concept of negotiation feedback using a novel data structure, an Agreement Table (AT), is proposed to expedite the negotiation process. The paper also proposes a multi-attribute-based utility model which is based on the novel understanding that if the price, response time and other such attributes of a service are changed appropriately with a change in quality, then the utility of the service should remain intact. In support of the presented approach, a prototype system providing negotiation between SWSs is implemented. The presented work is evaluated against existing similar works and its advantages are reported.